Introduction and implementation of an immunization information system in the Indonesian province of Daerah Istimewa Yogyakarta: lessons for scaling-up - Sulistyawati Sulistyawati; Trisno Agung Wibowo; Rokhmayanti Rokhmayanti; Andri Setyo Dwi Nugroho; Tri Wahyuni Sukesi; Siti Kurnia Widi Hastuti; Surahma Asti Mulasari; Marta Feletto (BMC, 2023)
Abstract Background Immunization is critical to saving children from infections. To increase vaccination coverage, valid and real-time data are needed. Accordingly, it is essential to have a good report system that serves as defaulter tracking to prevent children's immunization failure. The Daerah Istimewa Yogyakarta (DIY) Health Office introduced an electronic immunization registry and successfully implemented it for more than five years. It is the only individual-based record system in Indonesia that has been sustainably operated for a long time. Yet, no systematic assessment of this system has been conducted to date. This study examines the Sistem Informasi Imunisasi Terpadu (SIMUNDU) introduction and implementation process with a view to extracting lessons that could inform scalability and sustainability across the country. Methods This study used an explanatory sequential mixed-method design, which collected quantitative data from 142 participants and qualitative data from nine participants. The data entry clerk at a health facility was systematically selected to participate in the survey, while in the key informant interview, the informant was selected based on the survey result. A descriptive and thematic approach was adopted to analyze the quantitative and qualitative data. Results from across the two approaches were integrated for comparison and contrast. Results Findings are presented according to three core themes that emerged from the data: system strengths, potential threats, weakness and opportunities for scaling-up. Strengths, i.e., factors contributing to the success of SIMUNDU, include management, system performance, people's behavior, and resources. Potential threats to sustaining the system include individual capacity, technical or system issues, and high workload. Opportunities - i.e., a promising factor that influences the SIMUNDU ability to operate sustainably - such as continuity, expectation, and the possibility of scaling up. Conclusions SIMUNDU is a promising innovation for Indonesia, beyond DIY. There is agreement about the potential for scaling up this IIS to other provinces. The experience of implementing this system in DIY over the past five years has shown that the benefits outweigh the challenges, and SIMUNDU has grown into a robust yet user-friendly system.